CHROMIUM (III) COMPLEX OF 2-AMINO-3-CARBOMETHOXY-4,5,6,7-TETRAHYDROBENZO[B] THIOPHENE: SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY - EMMANUEL SOPBUÉ FONDJO; DÉSIRE ANDRÉ SIÉWÉ; JEAN DE DIEU TAMOKOU; STEVE ENDEGUELE EKOM; KAMAL SOREL DJEUKOUA DIMO; GISCARD DOUNGMO; MALLORY E. WALTERS; APPOLINNAIRE TSOPMO; PETER F. W. SIMON; JULES-ROGER KUIATE (Journal of the Chilean Chemical Society, 2020)
A new chromium (III) coordination compound of 2-amino-3-carbomethoxy-4,5,6,7-tetrahydrobenzo[b]thiophene (ACTT) (3)  with Cr(NO3)3.9H2O in methanol at room temperature for 48 hours has been prepared. The composition of the new complex compound (4) has been confirmed by a number of instrumental methods including IR, NMR, MS and elemental analysis. It was found  that  the ACTT ligand behaves as bidentate  chelating  agent  and  coordinates to  the  central metal ion  through  the nitrogen atom of the amino-group and the oxygen atom of the  carbonyl function of the ester group. The results showed that in the coordination sphere of the complex, the metal ion is coordinated by three chelating ACTT ligands. In the structure of the cation core [Cr(ACTT)3]3+, the three ACTT ligands are linked to the chromium ion through three Cr-N and three Cr-O bonds forming a square bipyramidal geometry. The metal complex and the ACTT ligand were screened for their antimicrobial activities against several strains of bacteria (Staphylococcus aureus ATCC25923, Escherichia coli S2 (1), Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa ATCC27853, Shigella flexneri SDINT) and fungi (Candida albicans ATCC10231, Candida tropicalis PK233, Cryptococcus neoformans H99). The chromium complex showed promising antimicrobial activity against the microorganisms with minimum inhibitory values between 4 and 16 μg/mL.